THE CORRELATION BETWEEN STUDENTS’ READING INTEREST AND THEIR READING SPEED - Sukarti, Ratri; Supriusman, Supriusman; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The objective of the research was to find out whether there is a significant correlation between students’ reading interest and their reading speed. The subject of this research was the fifth semester students of English Study Program of FKIP UR 2020. This quantitative research used a questionnaire and reading speed tests. The data were collected Online using Google Form. The total number of samples (N) is 36. The average score of reading interest (variable X) is 2429 and the average score of reading speed (variable Y) is 8351. The sum of multiple score of both variables (XY) is 571004.7. The sum of quadrate score of reading interest (X2) is 167525 and the sum of quadrate of reading speed (Y2) is 1985457. Students’ reading speed is categorized into average level with the average score 231.97. The result of the correlation index between variable X and variable Y is 0.57. and this research showed that the correlation between students’ reading interest and their reading speed is in moderate level.Key Words: Correlation, Reading Interest, Reading Speed